Desire for birth spacing or limiting and non-use of long acting and permanent contraceptive methods among married women of reproductive age in Aksum Town, North Ethiopia. Issue 1 (December 2016) - Haile, Kebede; Gebremedhin, Meresa; Berhane, Haileselasie; Gebremedhin, Tirhas; Abraha, Alem; Berhe, Negassie; Haile, Tewodros; Gigar, Goitom; Girma, Yonas
Abstract Background Long acting and permanent contraceptive methods are the most effective family planning (FP) methods to prevent pregnancy and thereby averting adverse consequences of too many and ill-timed pregnancies. However, long acting and permanent contraceptive methods (LAPMs) are underutilized in Ethiopia for little documented reasons. Therefore, this study is aimed to assess magnitude and factors associated with desire for birth spacing for at least 2 years or limiting child bearing and non-use of LAPMs among married women of reproductive age in Aksum town, Northern Ethiopia. Methods A community-based cross-sectional study was conducted in Aksum town, North Ethiopia from May to June, 2015 among 779 randomly selected married women of reproductive age. Data were collected using interviewer administered pre-tested questionnaire. Data were entered using Epi-Info version 6.04 and exported to SPSS version 16 for analysis. Multivariate logistic regression models were fitted to identify factors associated with desire for birth spacing or limiting and not using LAPMs. Results The total desire for birth spacing or limiting was 69 % and amongst those women 85.2 % were not using LAPM. Education, occupation, husband's attitude towards LAPMs, age, number of pregnancy, regular media exposure and decider on the number of children to bear were significantly associated with desire for birth spacing or limiting. Moreover; education, occupation, husband's attitude towards LAPMs, discussion on family planning with husband, knowledge, attitude and intention to use LAPMs were significantly associated with not using LAPMs. Conclusion Desire for birth spacing or limiting and not using LAPMs is very high in the study area. Therefore, increasing access to family planning information and services with special emphasis on LAPMs and male involvement in the program are very important.